Pengembangan Media Pembelajaran Interaktif Berbasis Komputer untuk Peserta Didik Mata Pelajaran Teknik Kendaraan Ringan - Sukoco Sukoco; Sutiman Sutiman; Muhkamad Wakid (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This study aimed to develop interactive teaching media for the subject of Diesel Motorcycle Fuel System at Vocational High Schools. This study was categorised into Research and Development. To examine the effect of the developed media, two classes at SMK Negeri 2 Pengasih were selected as the subjects of this study. The data analysis techniques employed descriptive statistical technique and T-test. The results revealed: 1) relatively, there is not Vocational High School teachers who use interactive media learning for the subject of Diesel Motorcycle Fuel System. The most widely used media were power point presentations. 2) Interactive computer-based media can be developed for teaching meterials of Diesel Motorcycle Fuel System. 3) Based on the experiment, the developed instructional media is effective in the learning process. 4). The interactive media foster better learning achievement than the power point media does.